Support the Troops: Gulf War Homecomings and a New Politics of Military Celebration. Issue 1 (13th February 2019) - Fitzgerald, David
Abstract : The celebrations that took place in the aftermath of the Persian Gulf War of 1991 stood out as the largest seen in the United States since the end of World War II, as hundreds of thousands of troops marched in triumphant parades in almost every major American city and in hundreds of small towns. But the pageantry did not simply celebrate American military and technological prowess. Spectators at these parades also engaged in a novel form of patriotism that emphasized unquestioning support for the troops. Representing a crucial moment in the American public's deepening veneration for U.S. soldiers and veterans, the Gulf War celebrations marked a turning point when the Vietnam-era image of the soldier as a broken or rebellious draftee was finally and purposefully eclipsed by the notion of the volunteer service member as hero.